P12 Suppression of fractional exhaled nitric oxide with directly observed inhaled corticosteroid therapy: is it a useful test in routine clinical practice?. (15th November 2017) - Faruqi, S; Thompson, J; Watkins, K; Cummings, H; Jackson, N; Prakash, A; Crooks, MG
Abstract : Introduction: Measurement of fractional exhaled nitric oxide (FeNO) is an easy to perform non-invasive test and surrogate marker of eosinophilic airway inflammation. It has been suggested that suppression of FeNO following a week of directly observed inhaled corticosteroid (ICS) therapy provides objective evidence of non-adherence. Though guidelines for the prescription of novel steroid sparing agents recommend this strategy as part of evaluation, it has not been rigorously evaluated in routine clinical practice. We report the outcomes of using this strategy as part of standard clinical care in our centre. Methods: Consecutive consenting patients with FeNO levels greater than 45 ppb on two occasions who were adherent to prescribed therapy on the basis of clinical history, and meeting criteria for initiation of biological therapy undertook directly observed ICS therapy – supervised (DOTS) over 8 days. In this, patients existing ICS/LABA combination inhalers were changed to once daily fluticasone/vilanterol (Relvar 184/22). Inhaler technique was taught by a specialist nurse and inhaled therapy taken under direct supervision (in person or remotely via Skype). FeNO, spirometry, eosinophil count and the Asthma Control Questionnaire −7 (ACQ-7) were recorded on the first and last days. FeNO was also recorded on day 4. Data are presented as mean ±SD. Results: Sixteen subjects (7 males, age 43±18 years) completed assessments (1 did not have day 4 FeNO value). All but one had ≥80% prescription pick-up rates checked with GP records. FeNO levels decreased from 121±63 ppb to 71±36 ppb at day 4 and 66±43 ppb at day 8 (p<0.01). 10 subjects had significant FeNO suppression by day 4 (figure 1 ). ACQ-7 score improved from 2.7±1.2 to 1.7±1.1 (p<0.01). Eosinophil count (0.65±0.51) and percent predicted FEV1 (79±19) did not change significantly. Conclusion: Combining the use of once a day therapy with remote assessment using appropriate technology, FeNO suppression is a feasible objective test of adherence in the routine clinical setting. Despite appropriate refill collection rates over half of subjects were identified as non-adherent to inhaled therapy. Although these individuals did not commence biological therapy, improvements have been sustained. We recommend routine use of this assessment in severe asthma services.